2004
DOI: 10.1002/cncr.20487
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic adenoma of the pancreas

Abstract: BACKGROUND.Cytology literature on pancreatic microcystic adenoma is sparse. It is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 23 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Contaminating glandular cells may be interpreted as atypical cells or neoplastic mucinous cyst. 8,10 In a retrospective morphologic study, only 5/51 (10%) cases were correctly identified as SCA on EUS-FNA. 11 Rest of the cases was either diagnosed, as benign ductal and acinar cells not otherwise specified diagnostic, pseudocyst, or mucinous cystic neoplasm (MCN).…”
Section: Pitfallsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contaminating glandular cells may be interpreted as atypical cells or neoplastic mucinous cyst. 8,10 In a retrospective morphologic study, only 5/51 (10%) cases were correctly identified as SCA on EUS-FNA. 11 Rest of the cases was either diagnosed, as benign ductal and acinar cells not otherwise specified diagnostic, pseudocyst, or mucinous cystic neoplasm (MCN).…”
Section: Pitfallsmentioning
confidence: 99%
“…7 Cytoplasm is scant, pale, foamy, and vacuolated. 7,8 This later finding may mimic macrophages and may result in a false-negative diagnosis.…”
Section: Cytologymentioning
confidence: 99%
“…A “honeycomb” appearance on CT or MRI, associated with a central scar that may or may not be calcified, is characteristic for microcystic variant 16, 17, 22, 2931 . However, the diagnosis is often not accomplished preoperatively by imaging studies.…”
Section: Serous Neoplasmsmentioning
confidence: 99%
“…The cytoplasm is usually cleared or vacuolated. However, the cells are frequently stripped of cytoplasm, showing only small, round nuclei with fine but dense, homogenous nuclear chromatin 31, 36, 39 .…”
Section: Serous Neoplasmsmentioning
confidence: 99%
“…This did not include reports of the use of FNA for the diagnosis that lack a description of the cytomorphologic features of the case(s). These reports are collected, reviewed and compared with the current findings [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. …”
Section: Methodsmentioning
confidence: 99%